PENGARUH BLENDED LEARNING BERBANTUAN LAB. VIRTUAL PhET DAN GOOGLE CLASSROOM TERHADAP HASIL BELAJAR FISIKA PADA SISWA KELAS X SMA NEGERI 1 TORUE KAB. PARIGI MOUTONG - Artawan, I Made Doni; Syamsu, Syamsu (Universitas Tadulako, 2022)
This research aims to determine the effect of blended learning assisted by the lab. virtual PhET and the google classroom online platform on physics learning outcomes in 10th grader of SMA Negeri 1 Torue in Kab. Parigi Moutong. The type of research conducted is a quasi-experimental design with